Analisis Program Pembasaan Literasi Terhadap Keterampilan Membaca dan Menulis Siswa Kelas V SDN 3 Pancor - Numina; Zohrani; Hamdi, Zulfadli (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstrack: This study aims to analyze the Literacy Habituation Program on the Reading and Writing Skills of Fifth Grade Students at SDN 3 Pancor in the 2025/2026 academic year. The research used descriptive qualitative research with data collection techniques including observation, interviews, and documentation to obtain the necessary data. Data analysis techniques used include data collection, data reduction, verification, and conclusion drawing. The literacy habituation program is a structured program involving students, educational institutions, and parents, with the aim of improving community literacy skills. The literacy habituation program has a positive impact on students' reading and writing skills. Based on the results and discussion of the research on the Analysis of the Literacy Habituation Program on the Reading and Writing Skills of Fifth Grade Students at SDN 3 Pancor, it can be concluded that the literacy motivation of students at SDN 3 Pancor, particularly fifth graders, is quite good. This is evidenced by the large number of students participating in school literacy activities, the existence of a text-rich environment, student reading journals, and improved student learning outcomes on educational report cards. Every program inevitably has challenges or obstacles, and the challenges at SDN 3 Pancor include limited library facilities and a lack of diverse reading materials. The school consistently seeks solutions and complements these shortcomings to achieve the goals of the literacy habituation program at SDN 3 Pancor. One solution is utilizing the digital library, establishing a text-rich environment, and establishing a reading corner. Abstrak: Penelitian ini bertujuan untuk Menganalisis Program Pembiasaan Literasi Terhadap Keterampilan Membaca dan Menulis Kelas V SDN 3 Pancor Tahun 2025/2026. Jenis penelitian yang digunakan yaitu penelitian kualitatif deskriptif dengan teknik pengumpulan data yaitu observasi, wawancara dan dokumentasi untuk mendapatkan data yang diperlukan. Program pembiasaan literasi merupakan program yang terstruktur yang melibatkan peserta didik, lembaga pendidikan, dan orang tua, dengan tujuan untuk meningkatkan keterampilan literasi masyarakat. Adanya program pembiasaan literasi memberikan dampak yang baik bagi keterampilan membaca dan menulis peserta didik. Berdasarkan hasil serta pembahasan penelitian tentang Analisis Program Pembiasaan Literasi Terhadap Keterampilan Membaca dan Menulis Peserta didik Kelas V SDN 3 Pancor, dapat disimpulkan bahwa motivasi literasi peserta didik di SDN 3 Pancor khususnya kelas V yaitu cukup baik, hal ini dibuktikan dengan banyaknya peserta didik yang berpartisipasi pada kegiatan literasi sekolah, adanya lingkungan kaya teks, jurnal baca siswa, dan meningkatnya hasil belajar peserta didik pada raport pendidikan. Setiap program pastinya memiliki kendala atau hambatan yang dialami, adapun kendala yang ada di SDN 3 Pancor yaitu fasilitas diperpustakaan yang masih terbatas dan kurangnya variasi bahan bacaan. Adanya kendala tersebut pihak sekolah mengupayakan kelengkapan fasilitas sekolah terutama bahan bacaan peserta didik, memanfaatkan perpustakaan digital, mengadakan lingkungan kaya teks, pojok baca dan mengupayakan suasana kegiatan literasi yang menyenangkan.